Gender, Social Change and Spiritual Power: Charismatic Christianity in Ghana - Soothill, Jane E (Studies of Religion in Africa Ser., 2007)
Against a backdrop of debate concerning the role of Pentecostalism as a mediator of 'modernity', this book examines the interaction between charismatic Christianity, spiritual power and gendered social change in contemporary Ghana.